Interactive Domestic House Cat Care Information Courseware (i-Cat) / Nor Syamimi Abdul Manan - Abdul Manan, Nor Syamimi (2016)
Interactive courseware can improve learning for user and this interactive ways also can motivate user to learn it by them because this interactivity and fun content might be available. The development of information courseware is to help the user to get the right information on caring their domestic house cat. The main target of this information courseware is to the cat’s owner itself. This project .is to create interactivity information multimedia courseware which will guide cat’s owner to take care of their cat in such proper ways. User also can access to this courseware at anytime and anywhere. This information multimedia courseware is not boring as traditional teaching style because it is contains interactivity between the courseware and the user. Besides, this information multimedia courseware provides few activities to the user. ADDIE model has been chosen to be a guideline in developing this courseware. This method contains of five phase which are analysis, design, develop, implement and evaluate. In order to develop courseware, there is some interview has been made in the analysis phase in which that come out with the modules needed in the courseware. After the development process finished, the courseware been evaluated by users and expert users. This evaluation been made in order to know whether the courseware fulfil the requirement needed by the users or not. There are 30 respondents and three experts been evaluate this i-Cat. There are total of 6 construct in the questionnaire. The construct consists of design interface, usability, activities, navigation and multimedia element. Based on evaluation been made, construct E shows the highest mean among all construct is 4.30 which is multimedia element (image, text and animation). Based on this construct, the highest mean item is E2 and E6 which is the image use is suitable and the quality is good and overall, I am satisfied with the image, text and animation of this courseware. For future enhancement, the courseware will be improve in term of providing more images so that can give a quick glimpse to the user.